Enhancing Consumer Decision-Making in Skincare: Implementation of the VIKOR Method for Product Recommendation Systems - Diah Arifah Prastiningtyas; Greta Septy Purwiantono; Febry Eka Purwiantono; Addin Aditya (Teknika, 2025)
The challenge of selecting the most suitable skincare products, particularly sunscreens, has become increasingly complex due to the overwhelming variety of choices available on the market. Consumers are often confronted with a plethora of products, making it difficult to discern which one best suits their needs. This study seeks to address this issue by employing the VIKOR multi-criteria decision-making (MCDM) method, which offers a structured approach to product selection based on various factors that are highly relevant to consumers. The VIKOR method, which focuses on minimizing regret and finding the closest compromise solution, is especially suited for handling decisions that involve conflicting criteria. In this study, five key criteria—skin type, brand origin, price, SPF rating, and UVA protection grade—were identified as being of particular importance to consumers. A dataset of 175 sunscreens formulated for oily skin and produced locally was systematically analyzed using the VIKOR algorithm. This method enabled the normalization and aggregation of diverse criteria, allowing for an objective, data-driven comparison of the products. The VIKOR-based approach efficiently ranked the sunscreens and identified AZARINE Hydramax-C Sunscreen Serum as the optimal product. This sunscreen achieved the lowest Q value of 0.07, signifying that it represented the best compromise solution across all criteria. The study’s findings not only highlight the practical value of advanced decision-making tools in the context of consumer product selection but also contribute to broader discussions on consumer behavior and decision-making frameworks. By demonstrating the efficacy of the VIKOR method, this research paves the way for its future application in various industries, offering a replicable and adaptable model for improving decision processes in consumer goods selection across diverse markets.